Three moss novelties in the flora of North Macedonia - Papp, Beáta; Pantović, Jovana P.; Szurdoki, Erzsébet; Sabovljević, Marko (Hacquetia, 2024)
Three moss species are recorded for the first time in the Republic of North Macedonia. These are Brachytheciastrum dieckei, Kiaeria starkei and Orthotrichum schimperi. The details on records are given including distribution, georeferences and ecology.